Studi Literatur: Penerapan Living Qur’an pada Pembelajaran di Sekolah - Arrasyid, Ihsan Auliya; Hikmah, Aida Nurul (YASIN, 2025)
This study aims to examine the implementation of the Living Qur'an concept in the learning process in schools from PAUD to SMA/MA. This concept interprets the Qur'an not only as a reading text, but as a guideline for life that is implemented in daily educational activities. The background of this study is taken from the importance of forming student character based on contextual and applicable Qur'anic values. This study uses a literature study method with a qualitative descriptive approach. Data sources were obtained from 14 scientific articles published in the last ten years. Analysis was carried out using source triangulation techniques to maintain the validity of the findings. The results of the study show that the implementation of the Living Qur'an is carried out through various approaches according to the level of education. In PAUD, practice is carried out through tarbiyah, tahajji, and tahfiz methods. In SD/MI, Qur'anic values ​​are integrated through reading surahs, calligraphy, and Asmaul Husna. In SMP/MTs, creative methods such as storytelling and tadabbur are used. While in SMA/MA it is carried out through the tasmi' program and Qur'an literacy. This study concludes that Living Qur’an is an effective strategy in instilling Islamic character if supported by a supportive educational environment and competent teachers.